Prevalence of unused medications and determinants among the general public in Addis Ababa, Ethiopia - Sefefe Geremew; Wondim Ayenew; Dawit Teshome Gebregeorgise; Bruck Messele Habte (BMC, 2024)
Abstract Background Accumulation, improper storage, and disposal of unused medications in the households have become a growing public health, environmental and economic concern. However, the magnitude, reasons, and disposal practices of the problems are not well studied in Addis Ababa, the capital city of Ethiopia. Therefore, this study aims to assess the prevalence and determinants of unused medications at household levels in Addis Ababa, Ethiopia. Methods A cross-sectional study design was used to collect data in Addis Ababa from April to May 2021. A total of 759 households in the Gulele and Lideta sub-cities were included in the survey using systematic random sampling techniques. Data was collected using an interviewer administered questionnaire and structured observation checklist. Multivariable logistic regression model was used to identify factors associated with unused medications. Data analysis was done using SPSS version 21. Results Among the surveyed households, 463 (61%) had unused medications of which anti-pains (30%) and anti-microbials (29%) were found to be the most common classes. The main reasons for the presence of unused medications were saving for future use (35.8%) and 'relief' or disappearance of symptoms (23.8%). The majority of households (69.2%) used household garbage for the disposal of their unused medications. A multivariable logistic regression analysis identified households who earned higher incomes, namely 8,001-12,000 ETB (AOR = 2.6 (1.2-5.7)) and more than 12,000 ETB (AOR = 2.9 (1.2-7.0)) were more likely to have unused medications. Conclusions There is a high prevalence of unused medications and unsafe disposal practice in households of Addis Ababa. Education about the rational use and safe disposal practice of prescribed medications should be given to the community. The government should come up with appropriate legal frameworks and device appropriate collection and disposal mechanism for unused medications emanating from households.